Association between Household Waste Management on the Presence of Disease Vectors in Residential Environments - Jernita Sinaga; Joice J Bana; Vinsensius Manek Ati; Andriani Ninda Momo; Kristina Moi Nono (CV. Get Press Indonesia, 2026)
Improper household waste management is a major risk factor for the presence of disease vectors in residential environments. This study aimed to analyze the association between household waste management and the presence of disease vectors in residential areas in Medan Marelan Subdistrict, Medan City, Indonesia. This research employed a quantitative analytic design with a cross-sectional approach. A total of 120 households were selected using simple random sampling. Data were collected through structured interviews and environmental observations. Data analysis was conducted using univariate and bivariate methods, including the Chi-square test with a 95% confidence level and Odds Ratio (OR) analysis. The results showed that the majority of respondents had poor waste management practices (61.7%), and disease vectors were present in 65.0% of households. Statistical analysis indicated a significant association between household waste management and the presence of disease vectors (p = 0.001), with an OR value of 6.67 (95% CI: 2.85–15.62). This finding suggests that households with poor waste management were 6.67 times more likely to have disease vectors compared to those with proper waste management. It can be concluded that household waste management has a significant association with the presence of disease vectors in residential environments. Therefore, strengthening community education regarding waste management, improving sanitation facilities, and increasing collaboration between health workers and local communities are important to support environmental sanitation and reduce vector-related health risks.